Market Strategy Development and Implementation for a Specialty Chemical Company in Asia - Xie, Wenbing (2006)
Facing the challenge of fierce competition in the conditioning polymers in AsianÃÂÃÂ¢ÃÂÃÂÃÂÃÂs shampoo market, Rhodia Novecare needs to proactively formulate and implement a market strategy to defend and even increase market share in a long run. An industry analysis was conducted to assess the market pressures from new entrants, substitution, supplier and buyer powers, and internal rivalry. Three strategies as an integral part of the market strategy have thus been developed in AsiaÃÂÃÂ¢ÃÂÃÂÃÂÃÂs conditioning polymer market for shampoo. The first strategy is the differentiation product development. The second strategy is cost-leadership. The third strategy is to develop a replicate product to market dominating product system by strategic alliance with a local manufacturer. To ensure the successful implementation of the above strategies, people factor is the most important. This implicates the organizational structure, organizational culture reinforcement, human resources management including the adequate appraisal, rewards and career development systems in place. Leadership and ownership is re-emphasized. Tactics and project methodologies are also very important in strategy implementation. The project pipeline methodology (ICPM) should be strictly implemented, especially after the pilot phase. Six sigma can be also applied to the R&D and business process at tactical level. It will help the optimization of business processes in a systematic and statistical way. Its applications will cultivate a result-oriented thinking behavior, as each six sigma project is evaluated with the returns in dollars. With the above market strategy development and their implementation in conditioning polymers, Rhodia Novecare will hold a leading position in this region. This means it is not only strongly positioned in market share and technology, but also in terms of its capability of launching innovative products and solutions or in knowledge creation.